2008
DOI: 10.1007/s11431-008-6009-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of raster resolution on landslide susceptibility mapping: A case study of Shenzhen

Abstract: Resolution has been playing a significant role in landslide susceptibility mapping and hazard assessment. Based on geographical information system (GIS) and information model, the effects of raster resolution on landslide susceptibility mapping are studied in a central area of Shenzhen, China. Eight factors are selected to calculate landslide susceptibility with eleven groups of different resolutions (5 to 190 m). It has been found that a finer resolution does not necessarily lead to a higher accuracy of lands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 17 publications
1
27
1
Order By: Relevance
“…Thus, the high spatial resolution (smaller grid cells) of the input datasets at the more detailed scale analysis provides more reliable information about the landslide-prone parts of Selinous catchment. This finding confirms the fact that the optimization of the resolution for LS assessment depends on the size of the study area [25]. By diminishing the size of grid cells as it was required from the diminution of the size of study area, higher landslide susceptibility mapping accuracy was achieved.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Thus, the high spatial resolution (smaller grid cells) of the input datasets at the more detailed scale analysis provides more reliable information about the landslide-prone parts of Selinous catchment. This finding confirms the fact that the optimization of the resolution for LS assessment depends on the size of the study area [25]. By diminishing the size of grid cells as it was required from the diminution of the size of study area, higher landslide susceptibility mapping accuracy was achieved.…”
Section: Discussionsupporting
confidence: 77%
“…In the last fifteen years, several studies have examined the effect of different grid cell sizes in LS assessment and mapping [23][24][25][26]. However, these studies have focused on the variations of the estimated LS, by changing the grid cell size and retaining same the analysis scale.…”
Section: Introductionmentioning
confidence: 99%
“…Overview of surveyed study areas ( Fig. 1), their surface area and number of total, shallow (SLS) and deep-seated landslides (DSLS) mapped together with the prevailing lithologies in those study areas according to the GTK consortium (2012) and the average annual precipitation as simulated by Thiery et al (2015).…”
Section: Study Area and Landslide Inventorymentioning
confidence: 99%
“…Various studies have demonstrated the influence of DEM resolution on the quality of the LSM results. However, there is no direct correlation between the resolution of DEM and the quality of the results of the LSM [10][11][12].…”
Section: Introductionmentioning
confidence: 99%